Steel surface treatment process for coupling surface nanocrystallization with vacuum carburization
Through the surface nano-coupled vacuum carburizing process, the problem of hardness concave points in the heat treatment of steel parts is solved, and the uniformity of hardness gradient and fatigue resistance are improved.
Patent Information
- Application Number
- CN202411733425.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-11-29
AI Technical Summary
In the prior art, steel parts are prone to form hardness concave points during heat treatment, resulting in surface softening layers, affecting fatigue performance and friction wear performance.
The surface treatment process of steel with surface nano-coupled vacuum carburization is adopted, including pre-oxidation, carburization treatment, heating quenching and tempering treatment, surface nano-coding treatment and secondary cycle cold back treatment, forming a surface structure with uniform and excessive hardness gradient.
The hardness concave points are eliminated, the surface fatigue resistance is improved, the material fatigue life is extended, and the surface hardness gradient uniformity is enhanced.
Smart Images

Figure CN119553217A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of thermochemical treatment, and in particular to a steel surface treatment process of surface nano-crystallization coupled with vacuum carburizing. Background Art
[0002] Surface modified steel refers to steel that has been surface processed or heat treated. Its characteristic is that the surface layer from the outer surface to a certain depth has different properties from the matrix. The aspects and degree of influence of this property vary depending on the surface processing or heat treatment process. The bending fatigue performance, contact fatigue performance, bonding performance and other indicators of surface modified steel are closely related to the load-bearing capacity, service life and reliability of the formed workpiece.
[0003] In the prior art, this type of steel uses strong infiltration and diffusion technology during heat treatment, but it is easy for the carbon enriched on the surface to diffuse towards the centripetal part for a long time under the pulse current, resulting in a decrease in the carbon content of the top layer of about 5-10μm. After quenching, martensite is not formed, and it is retained as residual austenite. Therefore, a softening layer appears within the range of 5-10μm on the surface, that is, hardness pits, which affects the surface hardness of the steel part. At the same time, due to the tensile stress caused by the contact load, the hardened layer on the surface of the workpiece initiates cracks during service, resulting in a fast crack initiation rate, which seriously affects the fatigue performance and friction and wear performance, and shortens the service time of the workpiece.
[0004] In order to further eliminate the softened layer on the surface of the steel body, the existing technology can use direct heating to austenitizing temperature, multiple quenching, tempering and other methods to improve the isotropy of the in-plane structure and improve the batch stability of processing. However, with the increase of processing methods, the time cost and energy consumption of the processing will also increase accordingly. The surface material is still easily affected by stress and cracks will occur, and the fatigue resistance is difficult to further improve. Summary of the invention
[0005] The purpose of the present invention is to provide a steel surface treatment process of surface nano-crystallization coupled with vacuum carburizing to solve the technical problem of hardness pits in steel parts in the prior art.
[0006] In order to solve the above technical problems, the present invention specifically provides the following technical solutions:
[0007] The present invention provides a steel surface treatment process of surface nano-crystallization coupled with vacuum carburizing, comprising the following steps:
[0008] S100, taking a steel part, and sequentially performing pre-oxidation and carburization treatment on the steel part, so that a hardened layer is formed on the surface of the steel part;
[0009] S200, directly heating the carburized steel part from the carburizing temperature to the austenitizing temperature, and then directly performing a rapid cooling and quenching treatment after heat preservation, and sequentially performing a deep cryogenic treatment and a medium temperature tempering on the quenched steel part, and repeating the process for multiple times to obtain a primary part;
[0010] S300, performing surface nano-processing on the primary component, so that a residual compressive stress surface layer with a thickness of millimeters is attached to the primary component, so as to obtain an intermediate component, wherein the hardness gradient of the intermediate component is uniformly transitioned from the surface layer to the core, and hardness pits are eliminated;
[0011] S400, performing a secondary cycle cold return treatment on the intermediate piece to obtain a finished piece.
[0012] As a preferred embodiment of the present invention, in S300, the surface nano-treatment conditions meet the following requirements:
[0013] The surfaces on both sides of the intermediate piece were subjected to surface nano-treatment with a total pressing depth of 120 μm on one side, a pressing depth of 10-15 mm per pass, a rotation speed of 1000 r / min, and a scanning processing rate of 4 mm / min.
[0014] As a preferred solution of the present invention, in S100, the pre-oxidation temperature range is 800°C to 950°C.
[0015] As a preferred embodiment of the present invention, in S100, the carburizing treatment is pulse vacuum carburizing;
[0016] The specific conditions of the carburizing treatment are as follows: the temperature range is 930°C to 980°C, the holding time is 10h to 40h, and a hardened layer with a depth range of 1.4mm to 2.5mm is formed on the surface of the steel part.
[0017] As a preferred solution of the present invention, during the carburizing process, the strong carburizing stage and the diffusion stage are repeated in sequence, and the time ratio of the strong carburizing stage to the diffusion stage is 1:2 to 1:3.
[0018] As a preferred embodiment of the present invention, in S200, the carburized steel part is directly heated from the carburizing temperature to the austenitizing temperature under a vacuum environment;
[0019] The austenitizing temperature is 1000°C to 1150°C;
[0020] The requirement for the holding time is: until the temperature inside and outside the steel part is uniform, so that the steel part is completely austenitized, and until the austenite grains stop growing.
[0021] As a preferred embodiment of the present invention, in S200, the cryogenic treatment comprises the following steps:
[0022] The temperature of the steel part is lowered to -120°C to -190°C at a cooling rate of 2.5 to 6.0°C / min, kept at that temperature for 2 to 4 hours, and then the steel part is heated back to room temperature at a heating rate of 2.0 to 10.0°C / min.
[0023] As a preferred solution of the present invention, in S200, the medium-temperature tempering temperature is 460° C.-540° C., and the holding time is 1 h to 4 h.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The present invention uses a self-developed new surface nano-process to process the surface of the steel part, so that the surface of the material is nano-scaled, and the generated compressive stress causes the residual austenite to transform into martensite, thereby increasing the hardness of the sub-surface layer, making the hardness gradient after carburizing evenly transition from the surface to the core, thereby eliminating the hardness pits of the material, and obtaining a metamorphic layer construction structure with better surface fatigue resistance;
[0026] The present invention combines vacuum carburizing treatment with surface nano-treatment to achieve a residual compressive stress surface layer with a thickness of millimeters. The residual compressive stress can offset part of the tensile stress caused by the contact load, thereby reducing the possibility of crack initiation. Under the compressive stress state, the stress concentration at the front end of the crack is reduced, slowing down the rate at which the crack spreads along the material. Under the action of the contact load, the residual compressive stress helps to distribute the contact stress more evenly, improves the load bearing capacity of the material in the contact area, reduces fatigue damage, and prolongs the fatigue life of the material.
[0027] The present invention combines vacuum carburizing treatment with surface nano-treatment and secondary cycle cold return treatment, which makes it easy to obtain a follow-up gradient structure layer and a larger strain / hardness gradient, and realize a residual compressive stress surface layer with a thickness of millimeters, thereby further improving the surface hardness of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. Obviously, the drawings in the following description are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.
[0029] Figure 1 A schematic flow chart of a steel surface treatment process of surface nano-crystallization coupled with vacuum carburizing is provided for the present invention;
[0030] Figure 2 The present invention provides a cross-sectional microhardness distribution diagram of the surface modified test steel shown in Example 1. DETAILED DESCRIPTION
[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] like Figure 1 As shown, the present invention provides a steel surface treatment process of surface nano-crystallization coupled with vacuum carburizing, comprising the following steps:
[0033] S100, taking a steel part, and sequentially performing pre-oxidation and carburization treatment on the steel part, so that a hardened layer is formed on the surface of the steel part;
[0034] S200, heating quenching and tempering treatment: the carburized steel part is directly heated from the carburizing temperature to the austenitizing temperature, and then directly subjected to rapid cooling quenching treatment after heat preservation, and the quenched steel part is subjected to deep cryogenic treatment and medium temperature tempering in sequence, and after repeated multiple times, a primary part is obtained;
[0035] S300, performing surface nano-processing on the primary component, so that a residual compressive stress surface layer with a thickness of millimeters is attached to the primary component, so as to obtain an intermediate component;
[0036] S400, performing a secondary cycle cold return treatment on the intermediate piece to obtain a finished piece.
[0037] The present invention performs carburizing treatment and subsequent deep quenching and tempering treatment on the metamorphic layer steel part, and can synthesize a hardened layer on the surface of the steel part, so that the surface hardness of the primary part is greater than the hardness of the steel part.
[0038] But the problem is that the tensile stress caused by the contact load of the primary part will increase the possibility of crack initiation. The stress concentration and dispersion at the front end of the crack may cause the surface crack of the workpiece to extend along the material, resulting in a decrease in the fatigue life of the material.
[0039] In order to improve the fatigue life of the material and slow down the crack initiation and expansion rate, the present invention uses a self-developed new surface nano-process to nano-nize the material surface. The generated compressive stress eliminates the residual austenite and transforms it into martensite to increase the hardness, so that the hardness gradient after carburizing is uniformly transitioned from the surface to the core to eliminate the hardness pits of the material. Combined with surface vacuum carburizing treatment, it is expected to obtain a metamorphic layer construction structure with better surface fatigue resistance. After the surface nano-processing of the primary parts treated by carburizing and tempering is carried out, the processing strain rate of the material surface is improved, the isotropy of the in-plane structure is improved, the batch stability of the processing is improved, and the thickness of the nano surface layer is controllable.
[0040] Specifically, after surface nano-treatment, a residual compressive stress surface layer with a thickness of millimeters is attached to the primary component. First, the existence of residual compressive stress improves the load-bearing capacity of the material in the contact area. When an external load acts on the surface of the material, the residual compressive stress can work together with the external load to improve the overall bearing capacity of the material.
[0041] It can be seen that the residual compressive stress in the surface layer is a very favorable condition for improving the contact fatigue performance. The reasons include but are not limited to: the residual compressive stress in the surface layer can offset part of the tensile stress caused by the contact load, thereby reducing the possibility of crack initiation; under the compressive stress state, the stress concentration at the front end of the crack is reduced, slowing down the rate of crack propagation along the material; under the action of the contact load, the residual compressive stress helps to distribute the contact stress more evenly, reduce local stress concentration, and thus reduce fatigue damage.
[0042] When an external load acts on the surface of a material, the residual compressive stress can work together with the external load to improve the overall bearing capacity of the material. The surface residual compressive stress can significantly extend the fatigue life of the material.
[0043] After the surface nano-treatment, the workpiece is subjected to a secondary cycle cold return treatment, so that the finished product is easy to obtain a gradient structural layer and a larger strain / hardness gradient, and achieve a residual compressive stress surface layer with a thickness of millimeters, further improving the surface hardness.
[0044] In a preferred embodiment of the present invention, the surface nano-treatment satisfies the following conditions:
[0045] The surfaces on both sides of the intermediate piece were subjected to surface nano-treatment with a total pressing depth of 120 μm on one side, a pressing depth of 10-15 mm per pass, a rotation speed of 1000 r / min, and a scanning processing rate of 4 mm / min.
[0046] The present invention forms a thick hardened layer on the surface of the workpiece through carburizing treatment, and after the carburizing treatment, the workpiece is optimized by surface nano-treatment, so that a residual compressive stress surface layer with controllable nano-surface thickness is generated on the surface of the steel part. On the one hand, it can offset part of the tensile stress caused by the contact load, thereby reducing the possibility of crack initiation; on the other hand, under the compressive stress state, the stress concentration at the front end of the crack is reduced, which slows down the rate of crack expansion along the material. At the same time, under the action of the contact load, the residual compressive stress helps to distribute the contact stress more evenly, reduce local stress concentration, and thus reduce fatigue damage.
[0047] In addition, the present invention adopts the following two methods to avoid the cracking problem caused by high internal stress caused by severe lattice distortion and a large amount of precipitated carbides after carburizing: the first is to eliminate stress through heat treatment, and directly heat to the austenitizing temperature after carburizing. The holding time requirement is to make the temperature inside and outside the steel part uniform so that the steel part is completely austenitized, and to stop the austenite grains from growing. After the holding time is completed, rapid cooling and quenching are directly carried out. At this time, the carbides caused by carburizing and the carbon atoms in the lattice gaps will all be dissolved in the austenite lattice, and the internal grains will be rearranged to eliminate the internal stress more thoroughly.
[0048] The existing method to avoid cracking of the workpiece is to slowly cool it in the furnace. During the slow cooling process, network carbides are easily precipitated along the grain boundaries, which is an important source of cracks. The second method to eliminate internal stress is cooling. After the workpiece is heated and quenched, it needs to be cryogenically treated immediately. By rapidly cooling the workpiece, the internal grains can be rearranged to eliminate the internal stress caused by lattice distortion.
[0049] In cryogenic treatment, the cryogenic parts are generally returned to room temperature before leaving the cryogenic treatment equipment. Depending on the requirements of the workpiece, they can also be directly returned to room temperature in the air. The post-treatment of cryogenic parts should remove the condensed moisture on the surface of the workpiece. It is also worth noting that the cryogenic parts should be tempered in time. The tempering process and parameters are determined according to the performance requirements of the workpiece.
[0050] Preferably, cryogenic treatment includes lowering the temperature of the workpiece to below -100°C, and keeping it warm, and then returning it to room temperature. Different cooling and heating rates will affect the elimination of internal stress in the workpiece. Too fast temperature change will easily lead to unevenness inside the material, causing the material to crack, and too slow will make it difficult to remove the internal stress. Therefore, the cooling rate of cryogenic treatment is limited to between 2.5 and 6.0°C / min, and the temperature of the workpiece is lowered to -120°C to -190°C, and then the temperature is stopped, and the temperature is kept for 2h to 4h before heating. The heating rate is limited to between 2.0 and 10.0°C / min, so that the workpiece returns to room temperature.
[0051] The specific cooling temperature and holding time are related to the material and size of the workpiece and can be adjusted according to actual production indicators.
[0052] In addition, pre-oxidation treatment is a necessary condition for successful carburizing treatment. It mainly targets the problem that the dense oxide film containing Cr affects the carburizing effect. The temperature range of pre-oxidation treatment is 800℃~950℃. Fe oxide continues to form on the surface of the workpiece with dense oxide film to loosen the dense oxide film and facilitate the penetration of carbon element during carburizing treatment.
[0053] In order to improve the carburizing efficiency, shorten the carburizing time, and meet the carburizing requirements of workpieces with different carburizing layers, the effective carburizing layer thickness of the carburizing treatment is 1.4mm~2.5mm; the specific conditions of the carburizing treatment are: the temperature range is 930℃~980℃, and the insulation time is 10h~40h. During the carburizing treatment, the strong carburizing stage and the diffusion stage are repeated in sequence, and the time of the strong carburizing stage and the diffusion stage is accurately controlled. The time ratio of the strong carburizing stage and the diffusion stage is 1:2~1:3. The surface-enriched carbon is diffused to the centripetal part for a long time under the pulse pulse current. Its main purpose is to increase the depth of the hardened layer on the steel surface and the hardness of the further formed workpiece surface, so that the friction and wear resistance and thermal hardness of the surface metamorphic layer steel are further improved.
[0054] Since the material is infiltrated with a very high concentration of carbon, a large amount of carbon infiltrated into the surface of the material will cause serious lattice distortion, causing great internal stress and easy cracking. At this time, if the tempering temperature is low, the energy is not enough to reduce the internal stress and stabilize the structure. If the tempering temperature is high and the time is long, it is easy to cause more carbon in the matrix to precipitate from the grain boundary, causing the carbide to grow and form a network of carbides at the grain boundary, resulting in intergranular cracking.
[0055] To this end, in the present invention, the medium-temperature tempering temperature is strictly controlled at 460°C-540°C, and the time is 1h-4h, so as to improve the overall (from the surface to the core) hardness and prevent the material from cracking. At the same time, tempering after quenching can further improve the overall (from the surface to the core) hardness, improve toughness, and improve comprehensive mechanical properties.
[0056] Repeated deep cryogenic treatment and medium temperature tempering processes on the quenched workpiece also play a very important role in solving the problems of softening layer and pits.
[0057] The present invention also generally includes the following steps:
[0058] 1) Perform preliminary heat treatment before carburizing. Gears with high distortion control requirements are preferably quenched and tempered. The structure after quenching and tempering is tempered troostite, the cementite is spherical, and the structure is uniform and fine;
[0059] 2) Prepare the workpiece after the preliminary heat treatment, ensure the workpiece surface is clean before carburizing, remove the oxide scale, rust, oil stains, stains, and perform non-destructive testing to ensure there are no cracks before carburizing, and take necessary anti-seepage protection measures at the anti-seepage parts;
[0060] 3) Repeat deep cooling and medium temperature tempering two or three times. The number of deep cooling and tempering can be determined according to the shape and size of the workpiece, generally 2 to 4 times. Tempering can stabilize the organization, eliminate internal stress, and precipitate carbides to play a strengthening role.
[0061] The above method is further described below by way of examples:
[0062] Embodiment 1:
[0063] 1. Select materials:
[0064] The Cr-containing Cr-containing standard CSS-42L stainless steel workpiece has a selected chemical composition of C, Cr, Mo, V, Ni, Co and Nb elements and accompanying impurity elements. In this example, the C element content is 0.16%, the Cr element content is 13.5%, the Mo element content is 4.5%, the Co element content is 13.0%, the Ni element content is 2.2%, the V element content is 0.58%, and the Nb element content is 0.03%.
[0065] 2. Heat treatment process
[0066] 1. Preparation
[0067] Gear workpieces with high requirements for distortion control are preferably quenched and tempered. After quenching and tempering, the structure is tempered troostite and cementite is prepared. The cementite is spherical and the structure is uniform and fine.
[0068] Before carburizing, ensure that the workpiece surface is clean and remove oxide scale, rust, oil stains and stains;
[0069] Conduct non-destructive testing to ensure there are no cracks before carburizing;
[0070] Take anti-seepage protection measures at anti-seepage areas.
[0071] 2. Pre-oxidation treatment
[0072] The workpiece is pre-oxidized at a temperature of 850°C, and Fe oxide is continuously formed on the surface of the workpiece having a dense oxide film under high temperature conditions, so that the dense oxide film is loose and porous, and the dense oxide film is mainly a dense oxide film containing Cr;
[0073] 3. Carburizing
[0074] The workpiece was subjected to pulse vacuum carburizing. During the carburizing process, the carburizing temperature was 960°C and the carburizing time was 28h.
[0075] The intensive infiltration stage and the diffusion stage are repeated in sequence, and the time ratio of the intensive infiltration stage to the diffusion stage is 1:2. The surface of the workpiece is gradually hardened, and the effective carburized layer thickness obtained by the carburizing treatment is 1.5mm.
[0076] 4. Heating and quenching
[0077] In a vacuum furnace, the carburized workpiece is directly heated from the carburizing temperature to the austenitizing temperature, i.e. 1080°C, and after being kept warm until the temperature inside and outside the workpiece is uniform, it is directly cooled and quenched with quenching oil for rapid cooling.
[0078] 5. Cryogenic treatment
[0079] After quenching, the temperature of the workpiece was lowered to -120°C at a cooling rate of 4°C / min and kept at this temperature for 3h;
[0080] The workpiece was heated back to room temperature (25°C) at a heating rate of 6°C / min.
[0081] 6. Medium temperature tempering
[0082] The cryogenically treated workpiece is heated to 480°C again, kept warm for 2.5 hours, and steps 5 and 6 are repeated three times to obtain a primary workpiece and proceed to the next step.
[0083] 8. Cleaning and testing
[0084] The surface oil stains of the primary parts were cleaned in time, and the hardness distribution and surface carbon content from the surface to the core were tested. The mass fraction of carbon on the surface of the primary parts was 1.2%, which met the requirements.
[0085] 9. Surface nano-treatment
[0086] The surfaces of both sides of the primary part were subjected to surface nano-treatment with a total pressing depth of 120 μm on one side, a pressing depth of 10-15 mm per pass, a rotation speed of 1000 r / min, and a scanning processing rate of 4 mm / min to obtain an intermediate part;
[0087] 10. Cooling
[0088] The intermediate piece is subjected to secondary cycle cold return treatment to obtain a finished piece, namely the surface modified structural test steel of the present invention.
[0089] Test, test the surface hardness of primary parts, intermediate parts and finished parts respectively, and the results are shown in Figure 2 shown.
[0090] exist Figure 2 In the figure, red represents the hardness after vacuum carburizing and tempering (primary part), green represents the hardness after surface nano-processing (intermediate part), and blue represents the hardness after surface nano-processing and tempering (finished part).
[0091] It can be seen that through vacuum carburizing + large surface deformation treatment, the surface hardness distribution and optimization control of the test steel are achieved, and the hardness of the outermost layer is further improved.
[0092] This embodiment uses a new surface nano-process developed by the company to optimize the surface hardness gradient distribution, explore the possibility of further improving the surface hardness, and obtain a metamorphic layer construction structure with better surface fatigue resistance. The compressive stress generated by surface nano-processing eliminates the residual austenite and transforms it into martensite to increase the hardness, so that the hardness gradient after carburizing is evenly transitioned from the surface to the core to eliminate hardness pits.
[0093] The above embodiments are only exemplary embodiments of the present application and are not intended to limit the present application. The protection scope of the present application is defined by the claims. Those skilled in the art may make various modifications or equivalent substitutions to the present application within the essence and protection scope of the present application, and such modifications or equivalent substitutions shall also be deemed to fall within the protection scope of the present application.
Claims
1. A steel surface treatment process of surface nano-crystallization coupled with vacuum carburizing, characterized in that: The steps include: S100, taking a steel part, and sequentially performing pre-oxidation and carburization treatment on the steel part, so that a hardened layer is formed on the surface of the steel part; S200, directly heating the carburized steel part from the carburizing temperature to the austenitizing temperature, and then directly performing rapid cooling and quenching treatment after heat preservation, and sequentially performing deep cryogenic treatment and medium temperature tempering on the quenched steel part to obtain a primary part; S300, performing surface nano-processing on the primary component, so that a residual compressive stress surface layer with a thickness of millimeters is attached to the primary component, so as to obtain an intermediate component, wherein the hardness gradient of the intermediate component is uniformly transitioned from the surface layer to the core, and hardness pits are eliminated; S400, performing a secondary cycle cold return treatment on the intermediate piece to obtain a finished piece.
2. A steel surface treatment process of surface nano-crystallization coupled with vacuum carburizing according to claim 1, characterized in that: In S300, the surface nano-treatment conditions meet the following requirements: The surfaces on both sides of the intermediate piece were subjected to surface nano-treatment with a total pressing depth of 120 μm on one side, a pressing depth of 10-15 mm per pass, a rotation speed of 1000 r / min, and a scanning processing rate of 4 mm / min.
3. The steel surface treatment process of surface nano-crystallization coupled with vacuum carburizing according to claim 1 is characterized in that: In S100, the pre-oxidation temperature ranges from 800°C to 950°C.
4. The steel surface treatment process of surface nano-crystallization coupled with vacuum carburizing according to claim 1 is characterized in that: In S100, the carburizing treatment is pulse vacuum carburizing; The specific conditions of the carburizing treatment are as follows: the temperature range is 930°C to 980°C, the holding time is 10h to 40h, and a hardened layer with a depth range of 1.4mm to 2.5mm is formed on the surface of the steel part.
5. The steel surface treatment process of surface nano-crystallization coupled with vacuum carburizing according to claim 1 is characterized in that: During the carburizing process, the strong carburizing stage and the diffusion stage are repeated in sequence, and the time ratio of the strong carburizing stage to the diffusion stage is 1:2 to 1:
3.
6. The steel surface treatment process of surface nano-crystallization coupled with vacuum carburizing according to claim 1, characterized in that: In S200, the carburized steel part is directly heated from the carburizing temperature to the austenitizing temperature under a vacuum environment; The austenitizing temperature is 1000°C to 1150°C; The requirement for the holding time is: until the temperature inside and outside the steel part is uniform, so that the steel part is completely austenitized, and until the austenite grains stop growing.
7. The steel surface treatment process of surface nano-crystallization coupled with vacuum carburizing according to claim 1, characterized in that: In S200, the cryogenic treatment includes the following steps: The temperature of the steel part is lowered to -120°C to -190°C at a cooling rate of 2.5 to 6.0°C / min, kept at that temperature for 2 to 4 hours, and then the steel part is heated back to room temperature at a heating rate of 2.0 to 10.0°C / min.
8. The steel surface treatment process of surface nano-crystallization coupled with vacuum carburizing according to claim 1, characterized in that: In S200, the medium-temperature tempering is performed at a temperature of 460° C. to 540° C., and the holding time is 1 h to 4 h.
Citation Information
Patent Citations
Heating treatment technology for piston pin
CN105238912A
Method for improving surface hardness of low-carbon high-alloy martensite bearing steel
CN116497262A
Chemical heat treatment process of surface-modified layer steel
CN117144288A
Surface modification method by shot-peening
JP2014054687A
Case carburized stainless steel alloy for high temperature applications
US5424028A